Links between the use of virtual learning environment and informatics curriculum in Lithuanian Lower Secondary School - Markauskaitė, Lina (Lietuvos matematikos rinkinys, 2003)
The paper analyses conceptual relations between the aims of the introduction of Virtual Learning Environments (VLE) and the informatics curriculum in the lower secondary school of Lithuania. The article investigates this issue from two opposite perspectives. First, it looks, how the VLE could help to attain the objectives of informatics curriculum. Second, it discusses, what skills and knowledge of students should be developed during the lessons of informatics in order to use VLE efficiently for different other teaching and learning objectives.